Inventory Of Seagrass Species On The Melonguane Timur Sub District Beach, Talaud Islands, North Sulawesi - Maabuat, Pience Veralyn; Kolondam, Beivy Jonathan (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2020)
Talaud Islands Regency is one of the administrative regions of North Sulawesi Province which holds high potential regarding biodiversity, especially marine organism. One example is the presence of seagrass species that support biologically and ecologically on the coast, but information regarding the types of seagrass in Talaud has not been fully recorded and is still small. For the Melonguane Timur District waters area was chosen as the initial step to collect data on seagrass types that exist as a biodiversity database in the Talaud Islands district and North Sulawesi Province. The research locations are North Tule and Bowongbaru Villages. The method used is the quadratic transect method and each seagrass in a 1m x 1 m quadratic plot was identified using a seagrass identification book. Based on the results of the study found four species of seagrass scattered on the station area, namely the family hydrocharitaceae and cymodoceae. Including the hydrocharitaceae family are Halophila ovalis and Halodule uninervis. The cymodoceae family is Cymodocea rotundata and Syringodium isoetifolium.